2018
DOI: 10.1007/s11060-018-2813-9
|View full text |Cite
|
Sign up to set email alerts
|

Salvage therapy outcomes for atypical meningioma

Abstract: Atypical menginomas demonstrate increased clinical aggressiveness characterized by recurrence and diminished survival. The optimal management of atypical meningioma in the recurrent setting is especially not well defined. To characterize outcomes following salvage treatment of recurrent atypical meningioma and to identify risk factors for further recurrence. Retrospective chart review was performed on 65 patients who underwent salvage treatment of atypical meningioma at a single institution. Data were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…WHO grading, MIB-1 proliferation activity, initial versus salvage treatment and the localization showed significant prognostic values in univariate analysis. These prognostic factors are well in line with several previous reports [15–17]. However, better prognosis of skull base and optic nerve sheath meningiomas in our study appears contrary to other publications.…”
Section: Discussionsupporting
confidence: 90%
“…WHO grading, MIB-1 proliferation activity, initial versus salvage treatment and the localization showed significant prognostic values in univariate analysis. These prognostic factors are well in line with several previous reports [15–17]. However, better prognosis of skull base and optic nerve sheath meningiomas in our study appears contrary to other publications.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the intrinsic morbidity of salvage surgery and radiotherapy for recurrent meningioma 53 55 , there is an urgent, unmet need for new therapies to treat patients with high grade or recurrent tumors 4 , 5 . We have shown that meningiomas with elevated ADC are at risk for high grade and recurrence 45 , 46 , and have identified molecular signatures associated with high ADC values in vivo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pontoriero et al [ 50 ] in 2022 reported use of a stereotactic radiosurgery boost in addition to IMRT to achieve an equivalent dose in 2 Gy fractions of 72.5 Gy to areas of gross residual WHO grade 2 meningiomas, reporting no serious toxicities among 16 patients. All 7 patients with primary WHO grade 2 meningioma and gross residual tumors after surgery achieved local control, but 4 of 9 patients with recurrent WHO grade 2 tumors developed in-field failures, underlining the fact that recurrent meningiomas are biologically more aggressive [ 51 ] and may frequently encode genetic and epigenetic alterations leading to treatment resistance [ 52 ]. Finally, historical series have also noted trends towards improved local control of high grade meningiomas with doses greater than 60 Gy in Boskos et al [ 53 ] and Hug et al [ 54 ], and greater than 53 Gy in Goldsmith et al [ 13 ].…”
Section: Efficacy and Safety Of Radiotherapy For Meningiomamentioning
confidence: 99%